EFEKTIVITAS PELAKSANAAN BIMBINGAN PERKAWINAN CALON PENGANTIN (BIMWIN) DI KABUPATEN PANDEGLANG - Tuti Via Listiani; Dita Arsyadina; Hunainah (STKIP Subang, 2026)
This study aims to analyze the effectiveness of Marriage Guidance (Bimwin) for prospective brides and grooms (catin) in Pandeglang Regency. Bimwin is a premarital guidance program organized by the Office of Religious Affairs (KUA) as a preventative measure to foster a harmonious, loving, and compassionate family. This study used a qualitative, descriptive approach, using observation and interviews as data collection techniques at nine KUA offices: Menes, Pulosari, Saketi, Majasari, Pandeglang, Karang Tanjung, Cadasari, Koroncong, and Kadu Hejo. Data analysis was conducted using descriptive qualitative methods to describe the implementation of Bimwin based on indicators of duration, frequency, content, and level of completion. The results indicate that the implementation of Bimwin in Pandeglang Regency is still varied and does not entirely meet ideal standards. Some KUAs, such as Saketi, have implemented Bimwin effectively with more structured duration and materials, while most other KUAs are still less than optimal due to limited duration, irregular frequency, and lack of depth of material. In general, the effectiveness of Bimwin for Pregnant Women and Brides in Pandeglang Regency remains suboptimal because it does not fully comply with the ideal implementation standards as outlined in the Minister of Religious Affairs Regulation concerning Marriage Guidance for Prospective Brides and Grooms. Therefore, improvements are needed in planning, implementation, and material standardization to maximize the program's objectives.